A Halogen‐Bonded Dimeric Resorcinarene Capsule1. (7th May 2015) - Beyeh, Ngong Kodiah; Pan, Fangfang; Rissanen, Kari
Abstract Iodine (I2) acts as a bifunctional halogen‐bond donor connecting two macrocyclic molecules of the bowl‐shaped halogen‐bond acceptor, N‐cyclohexyl ammonium resorcinarene chloride 1, to form the dimeric capsule [(1, 4‐dioxane)3@12(I2)2]. The dimeric capsule is constructed solely through halogen bonds and has a single cavity (V=511 Å3) large enough to encapsulate three 1, 4‐dioxane guest molecules.